Rate of cognitive decline in relation to sex after 60 years-of-age: A systematic review - Ferreira, Leandro; Ferreira Santos-Galduróz, Ruth; Ferri, Cleusa Pinheiro (Wiley, 2013)
Some studies have shown differences in specific cognitive ability domains between the sexes at 60 years-of-age. However is important to analyze whether the rate of cognitive decline is also similar between the sexes after this age. The present study examined previously published literature to investigate whether cognitive decline is distinct between men and women after the age of 60 years. A systematic review was carried out with the PubMed, LILACS and PsycINFO databases (2001-2011) using the following search terms: aging, aged, cognitive function, mild cognitive impairment, mental health and cognition. We analyzed longitudinal research that used neuropsychological tests for evaluating cognitive function, showed results separated by sex and that excluded participants with dementia. Elderly women showed better performance in tests of episodic memory, whereas elderly men had a better visuospatial ability. Only one study detected distinct rates of cognitive decline in specific tests between the sexes. Despite differences observed in some domains, most of the studies showed that this rate is similar between the sexes until the age of 80 years. It is unclear whether sex influences the rate of cognitive decline after the age of 80 years. The present review observed that sex does not determine the rate of cognitive decline between 60 and 80 years-of-age. The contextual and cultural factors that involve men and women might determine a distinct decline between them, rather than sex alone. © 2013 Japan Geriatrics Society.
Keywords: Aging; Cognition; Longitudinal studies; Neuropsychological tests; Sex